Predictors of survival from Acinetobacter in Saudi Arabian intensive care units: A prospective, one-year, six-city, ten-center cohort study - Ayman Kharaba; Haifa Algethamy; Mohamed A. Hussein; Fahad M. Al-Hameed; Adnan Alghamdi; Ammar Hamdan; Jehan Fatani; Alyaa Elhazmi; Hassan Alkhalaf; Ali Albshabshi; Hasan M. Al-Dorzi; Yaseen M. Arabi (Elsevier, 2022)
Background: Antibiotic-resistant Acinetobacter baumannii is a continuously-emerging worldwide health crisis, with mortality rates approaching 50% in intensive care unit (ICU) patients. The objective of this study was to evaluate regional, patient-related, and organism-related predictors of survival among critically-ill patients with confirmed Acinetobacter infection. Methods: This prospective cohort study was conducted within ten ICUs across six geographically- and climatologically-distinct cities across Saudi Arabia over 13 months. Results: Of 169 patients with confirmed Acinetobacter infection enrolled in the study, 80 (47.6%) died. Survivors were statistically younger, predominantly male, more likely to be admitted for trauma, less likely to have hypertension, diabetes, or have undergone hemodialysis, and more likely to have been treated with antibiotics prior to having a positive culture for Acinetobacter, but less likely to have received an aminoglycoside. Survivors also had lower baseline APACHE II and SOFA scores and were infected with stains of Acinetobacter that had less meropenem- or colistin-resistance. Multivariate analysis identified the following independent predictors of survival: younger age, lower ICU-day#1 APACHE-II and ICU-day#3 SOFA scores, being admitted for trauma, and having no history of hemodialysis. Conclusions: Patient-related factors outweigh regional and hospital-related factors as predictors of survival among critically-ill patients with Acinetobacter infection.